2006
DOI: 10.1073/pnas.0607465103
|View full text |Cite
|
Sign up to set email alerts
|

Podocin and MEC-2 bind cholesterol to regulate the activity of associated ion channels

Abstract: The prohibitin (PHB)-domain proteins are membrane proteins that regulate a variety of biological activities, including mechanosensation, osmotic homeostasis, and cell signaling, although the mechanism of this regulation is unknown. We have studied two members of this large protein family, MEC-2, which is needed for touch sensitivity in Caenorhabditis elegans, and Podocin, a protein involved in the function of the filtration barrier in the mammalian kidney, and find that both proteins bind cholesterol. This bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
287
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(309 citation statements)
references
References 36 publications
15
287
0
7
Order By: Relevance
“…Podocin may serve two closely related functions: the recruitment and/or stabilization of nephrin at the podocyte foot process, and the augmentation of nephrin signaling, perhaps by organizing specialized nephrin-containing microdomains [22]. In lipid microdomains, podocin clusters and regulates the transient receptor calcium channel (TRPC)-6 [23] and it has been suggested that this regulation gives the slit diaphragm the ability to act as a mechanosensor that enables the podocyte to remodel its cytoskeleton and contract its foot process in response to mechanical stimuli [24]. Finally, TRPC-6 is a critical controller of actin cytoskeleton.…”
Section: The Podocyte’s Strength and Weakness: Its Actin Cytoskeletonmentioning
confidence: 99%
“…Podocin may serve two closely related functions: the recruitment and/or stabilization of nephrin at the podocyte foot process, and the augmentation of nephrin signaling, perhaps by organizing specialized nephrin-containing microdomains [22]. In lipid microdomains, podocin clusters and regulates the transient receptor calcium channel (TRPC)-6 [23] and it has been suggested that this regulation gives the slit diaphragm the ability to act as a mechanosensor that enables the podocyte to remodel its cytoskeleton and contract its foot process in response to mechanical stimuli [24]. Finally, TRPC-6 is a critical controller of actin cytoskeleton.…”
Section: The Podocyte’s Strength and Weakness: Its Actin Cytoskeletonmentioning
confidence: 99%
“…Stomatin, podocin, MEC-2, UNC-24, and several other PHB-domain proteins have a hydrophobic [44] region N-terminally adjacent to the PHB domain [3,8,39,77]. This domain in MEC-2, stomatin, and podocin attaches the proteins to the inner leaflet of the plasma membrane [40].…”
Section: Proteins Required For Mechanosensationmentioning
confidence: 99%
“…In MEC-2, the domain is required for homooligomerization, localization to puncta, and amplification of MEC-4d currents in frog oocytes [98]. Recently, MEC-2 has also been shown to bind cholesterol; this binding requires the PHB domain and five amino acids in the adjacent hydrophobic region [40]. In HEK 293T cells, expression of MEC-2 can bind and recruit cholesterol to rat αENaC (a DEG/ENaC protein whose TM2 domain can substitute for that of MEC-4 in vivo [36]), and MEC-2 probably plays a similar role in C. elegans touch receptor neurons.…”
Section: Proteins Required For Mechanosensationmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice and humans, TRPC6 protein is expressed in kidney podocytes in close proximity to the filtration slits of the glomerular filter. Recent studies support the notion that TRPC6-mediated calcium signaling contributes to the maintenance of the glomerular slit diaphragm and the regulation of glomerular permselectivity (Huber et al, 2006). TRPC6 knockout mice display defective vasomotor control and a sensitized myogenic response, suggesting an important role in smooth muscle contractility (Dietrich et al 2005, Weissmann et al, 2006.…”
Section: Nih Public Accessmentioning
confidence: 76%